A leitura literária no livro didático: caminhos e perspectivas - Azevedo, Luciana Pereira (2021)
The goal of this work is to analyze the approach of Literature, promoted by the Portuguese Language textbook, in the 1st year of Elementary School. The purpose we are pursuing is investigating the idea that contribute to the growth of the literary reader. Our hypothesis is that although Literature is present in the textbook its approach does not effectively contribute to the development of the reader since it offers only a narrow contact with fragments of the literary text and and does not permit the reader to access the children's literature book. The research begins by identifying the significant presence of the textbook in Brazilian classrooms. In chapter 1, we outline a historical profile of the textbook, important to understand the protagonism of this kind material. The history of the PNLD and the specificities of the PNLD 2019 that we are trying here to describe, presented the BNCC as a guiding document for the distribution of content and the attendance of essential skills for the student. In this chapter, the corpus of this research refered to the 1st year professor's book in the Ápis collection, the most distributed book in PNLD 2019 and we deal with the issue of Literature schooling. The concept of literary reader's development is based on Antonio Candido, Viktor Chklovski, Roland Barthes, Tzvetan Todorov, Antoine Compagnon, Mario Vargas Llosa and Rildo Cosson. The chapter 2 shows the concept of childhood that goes through this work and the importance of children's literature. Maria Nikolajeva and Carole Scott, Sophie Van der Linden and Odilon Moraes support the understanding of the characteristics of the children's literature book. With this theoretical framework, we started with a qualitative analysis of three occurrences of Literature in the corpus and promoted a comparison with the original work. At this point, we confirm the hypothesis of this research by concluding that the textbook approach is insufficient and promote the aspects related to linguistic knowledge. In chapter 3, we discussed the importance of finding feasible editorial solutions for an appropriate broach to Literature in the textbook. Considering the existence of very unequal Brazilian socioeconomic scenario, most of the children will only have access to Literature through the textbook. We know that when the text of the original book is taken off to be used on the textbook, this will certainly impoverish the effect of meanings. It is possible to make options to avoid future Literature mutilations and, it is with this point of view that we selected occurrences in other textbooks approved in PNLD 2019. It was done to give visibility to good editorial solutions and the way to highlight some basic criteria that can guide didactic productions